Respuesta :
Answer:
x=ln(61)/ln(4)
Step-by-step explanation:
4^x+3=64
4^x=64-3
4^x=61
x=ln(61)/ln(4)
Equation equivalent to [tex]4^{x+3} =64[/tex] is equals to [tex]2^{2x+6} = 2^{6}[/tex].
What is equivalent?
" Equivalent is defined as when two or more algebraic expression or number have same result but different representation."
According to the question,
Given equation ,
[tex]4^{x+3} =64[/tex]
Represent equation in equivalent form
[tex]4^{x+3}[/tex] ≡ [tex]2^{2x+6}[/tex]
[tex]64 =4^{3}[/tex]
Therefore,
[tex]4^{3}[/tex] ≡ [tex]2^{6}[/tex]
Hence, equation [tex]4^{x+3} =64[/tex] is equivalent to [tex]2^{2x+6} = 2^{6}[/tex] .
Learn more about equivalent here
https://brainly.com/question/14672772
#SPJ3